EFEK DOMINO INDUKSI MATEMATIKA - Dandy Apviano (Journal on Mathematics Education Research (J-MER), 2020)
In integers we can determine a truth using mathematical induction. Mathematical induction is also a matter in the form of a framework because it does not have the same character as mathematical induction. Because there is a real form now we can more easily understand mathematical induction to determine its own truth. In this paper we want to determine the truth of mathematical induction in the domino effect. The basic domino effect is if the first domino card falls, the next card will fall because it gets a boost from the first card. this event will run continuously until the last card falls. This event is proportional to the character of mathematical induction if a (n) is true, a (n + 1) is also true where n is a positive integer.